Identification and functional analysis of AvLACS genes unveils their role in lipid homeostasis and waterlogging tolerance in kiwifruit (Actinidia valvata Dunn) - Zhang, Meijuan; Ye, Kaiyu; Gao, Jianyou; Liu, Shibiao; Liu, Ruonan; Chen, Yuexing; Zhao, Qian; Lei, Yushan; Li, Jiewei; Liu, Cuixia; Wang, Faming (Frontiers in Plant Science, 2025)
Long-chain acyl-CoA synthetases (LACSs) are involved in fatty acid metabolism and catabolism by converting free fatty acids to acyl-CoAs. They are essential for initiating β-oxidation of fatty acids and regulating lipid biosynthesis in plant growth and development, as well as in plant adaptation to various environmental stresses, including waterlogging stress. However, systematic identification and functional characterization of the LACS gene family have not been comprehensively studied in the waterlogging-tolerant kiwifruit germplasm Actinidia valvata Dunn. In this study, 22 AvLACS genes were identified within the A. valvata genome. The AvLACS genes were subsequently divided into five clusters on the basis of their phylogenetic relationships, and similar subcellular localizations, exon-intron structures, motif compositions, and protein tertiary structures were found within each cluster. Collinearity analysis identified 22 duplicated gene pairs in A. valvata, and these pairs have undergone purifying selection during evolution. Cis-acting element analysis revealed numerous hormone-responsive and stress-responsive elements in the promoter regions of the AvLACS genes. The expression levels of the AvLACS genes under waterlogging stress were determined using quantitative real-time PCR (qRT-PCR), and the results showed that the expression of the AvLACS1.1a/b, AvLACS1.2a, and AvLACS6a/b was significantly upregulated under waterlogging stress. Notably, AvLACS1.1a/b and AvLACS1.2a primarily facilitate short-term regulation of wax and triacylglycerol (TAG) synthesis, whereas AvLACS6a/b mediate TAG degradation through fatty acid β-oxidation during prolonged waterlogging. Transcriptome data revealed coordinated transcriptional regulation of TAG degradation pathway genes, which was supported by biochemical lipid profiling showing dynamic alterations in TAG content and degree of unsaturation correlated with waterlogging duration. These integrated molecular and biochemical data provide mechanistic insights highlighting distinct and coordinated roles of AvLACSs in lipid metabolic remodeling under waterlogging stress. These findings advance our understanding of the molecular mechanisms underlying waterlogging tolerance, and provide molecular targets and a theoretical basis for breeding waterlogging-tolerant kiwifruit and other crops.